Let's denote the number of people who ordered chicken as \( x \) and the number of people who ordered steak as \( y \). We know the following:
-
The total number of people: \[ x + y = 6 \]
-
The total cost of the dinners: \[ 14x + 17y = 99 \]
Now, we can solve these equations step by step.
First, from the first equation, we can express \( y \) in terms of \( x \): \[ y = 6 - x \]
Next, we substitute \( y \) into the second equation: \[ 14x + 17(6 - x) = 99 \]
Expanding the equation: \[ 14x + 102 - 17x = 99 \]
Combine like terms: \[ -3x + 102 = 99 \]
Now, isolate \( x \): \[ -3x = 99 - 102 \] \[ -3x = -3 \] \[ x = 1 \]
Now that we have \( x \), we can find \( y \): \[ y = 6 - x = 6 - 1 = 5 \]
Thus, the solution is:
- Number of people who ordered chicken: \( 1 \)
- Number of people who ordered steak: \( 5 \)
To verify:
Total cost: \[ 14(1) + 17(5) = 14 + 85 = 99 \]
This confirms that the calculations are correct. Therefore, the final answer is:
- 1 person ordered chicken and 5 people ordered steak.